ANALISIS DAMPAK PERCERAIAN ORANG TUA TERHADAP PENDIDIKAN ANAK - Syahbila Zalva; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
The family is an important place between individuals and groups and is the first social group. Meanwhile, children are a mandate from God who have the right to live and get love from parents. Children exist because of the relationship between husband and wife called marriage. However, if there is disharmony in the household between husband and wife, divorce occurs. The objectives achieved in this study are to know the impact of divorce on children’s education and also to know the steps to restore children’s education due to parental divorce. The research method that researchers use is literature review, in this study obtained 9 journals from google scholar, pubmed, and mendeley. Based on data from the Indonesian statistical agency, the number of divorce problems in this country reached 447,743 cases in 2021, then increased by 53.53% when compared to 2020 which amounted to 291,677 cases. This data show that more wives are filling for divorce against their husband. About 337,343 cases or 75.34% of existing divorce problems are due to contested divorce from the wife. Meanwhile, a total of 110,440 cases or 24.66% of divorce were caused by divorce from the husband. Divorce has a huge impact on children’s education both formally and informally. To overcome this problem, it is necessary to have good communication, provide support and provide a good environment for children